Perception of Facial Attractiveness from Static and Dynamic Stimuli. (February 2013) - Kościński, Krzysztof
Although people we meet in real life are usually seen in motion, research on facial attractiveness has predominantly been conducted on static facial images. This raises a question about ecological validity of results obtained in such studies. Recently, several studies endeavoured to determine the concordance between attractiveness of faces seen on photos and video clips, but their results are markedly divergent, frequently indicating no concordance. In the present study, the association between attractiveness of facial images and clips was tested on a larger sample than has previously been reported (106 females, 102 males), and features under the face owner's control (scalp and facial hair, makeup, mouth expression) were controlled for. Two types of facial images were used: photographs and frames extracted from films. Correlation coefficients between attractiveness of static and dynamic faces were high (about 0.7), did not depend on facial sex or image type (photograph/frame), and did not diminish when the covariates were controlled for. Furthermore, the importance of facial averageness, femininity/masculinity, symmetry, fattiness, skin health, and mouth expression for attractiveness proved similar for static and dynamic stimuli. This leads to the optimistic conclusion that results of studies relying on attractiveness assessments of static facial images are ecologically valid.